Answer:
Step-by-step explanation:
y = 3(4x + 1)^1/2 - 2x
dy/dx = 3*1/2(4x + 1)^-1/2 * 4 - 2
= 4 * 1.5 (4x + 1)^-1/2 - 2
= 6(4x + 1)^-1/2 - 2
= [6/√(4x + 1)] - 2
y = 3(4x + 1)^1/2 - 2x
∫3(4x + 1)^1/2 - 2x . dx
= 3 * 1/4 * (4x + 1)^3/2 / 3/2 - x^2 + C
= 3/4 * 2/3 (4x + 1)^3/2 - x^2 + C
= 1/2((4x + 1)^3/2 - 2x^2) + C.
230/10 = 23 with no remainder.
236/10 = 23 with remainder 6.
6 crayons were left over.
Answer:
x = 1 and y = 1
Step-by-step explanation:
7(1) minus 3(1) = 4
and 2(1) minus 1 = 1
just try and guess a number and try to solve the problem with that number, if it isn't the answer then repeat.
Answer:
Q1) x = 17.3
y = 8.7
Q2) d = 19
Step-by-step explanation:
Question 1
Angle = 60°
Hypotenuse = x
Adjacent = y
Opposite = 15
<u>Step 1: Find x</u>
Sin (angle) = opposite/hypotenuse
Sin (60°) = 15/x
x = 10√3 = 17.3
<u>Step 2: Find y</u>
Tan (angle) = opposite/adjacent
Tan (60°) = 15/y
y = 5√3 = 8.7
Question 2
<u>Step 1: Find the diagonal of the base</u>
c² = a²+b²
c² = 6² + 10²
c = 2√34 = 11.7
<u>Step 2: Find diagonal d</u>
c² = a² + b²
d² = 11.7² + 15²
d = 19
!!